Exploring legal and political-institutional determinants of the informal economy of Pakistan - Rizwana Hayat; Abdul Rashid (Cogent Economics & Finance, 2020)
In this paper, the size of the informal economy of Pakistan is determined by including the legal and political-institutional variables as determinants. By using the MIMIC model average estimate for the informal economy of Pakistan is 37.75 percent from 1995 to 2017. The study tries to explore the institutional implications of the informal economy for policymakers to reduce and control the informal economy in the developing country. Empirical results show that the most significant legal variable is Law and Order and the most important political variable is Religion in Politics for measuring the informal economy. Departing from existing studies, institutional determinants are explored in detail because these different institutional determinants may affect the informal economy differently in developed, developing, and underdeveloped countries. The policy formation process can be more effective in developing countries like Pakistan with consideration of the most relevant institutional factors in estimation.
Keywords: E26; O17; 330; informal economy; underground economy; formal and informal sectors; shadow economy; institutional arrangements; institutional quality; MIMIC model; Pakistan